Association between cannabinoid receptor type 2 Q63R variant and oligo/polyarticular juvenile idiopathic arthritis. (July 2015) - Bellini, G; Olivieri, AN; Grandone, A; Alessio, M; Gicchino, MF; Nobili, B; Perrone, L; Maione, S; Miraglia del Giudice, E; Rossi, F
<x xml:space="preserve">Abstract</x> Objectives: To investigate whether the functional variant Q63R of the cannabinoid 2 (CB2) receptor is associated with susceptibility to oligo/poly-articular juvenile idiopathic arthritis (JIA) and with its clinical features. Method: A total of 171 Italian children with oligoarticular/rheumatoid factor negative poly-articular JIA and 600 healthy controls were enrolled in the study and genotyped. Results: A significant difference in genotype distribution of the CB2 Q63R variant (CNR2 rs35761398) between oligo/poly-articular JIA patients and controls was found (p = 0.001). The R63 variant was associated with increased rates of relapse (p = 0.0001). Conclusions: This study indicates that the CB2 receptor contributes to susceptibility to oligo/polyarticular JIA and to the severity of its clinical course.